The Mediating Role of FoMO in the Influence of Discounts and Servicescape on Gym Membership Subscription Decisions - Ghalda Syadza Rafa Nafisah; Nyoman Sri Manik Parasari; Nilna Muna; Ni Putu Nina Eka Lestari (DINASTI RESEARCH, 2025)
This study examines how the Fear of Missing Out (FoMO) functions as a mediating variable in the relationship between Discounts and Servicescape on consumers’ decisions to subscribe at Yes Fitness in Bali. Increasing rivalry within the fitness sector encourages companies to create more efficient marketing approaches, such as price-related promotions, an engaging physical environment, and psychological tactics that generate urgency. A quantitative approach was adopted using purposive sampling, resulting in 257 valid respondents. The dataset was analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that Discounts and Servicescape have a significant impact on FoMO, and all variables significantly influence subscription decisions. FoMO is also proven to partially mediate the effect of Discounts and Servicescape on consumer subscription behavior. These results emphasize the strategic value of limited-time promotional offers, well-designed and appealing servicescapes and urgency-based communication strategies in encouraging consumers’ willingness to subscribe. The practical implications suggest that fitness centers can enhance their competitiveness by improving promotional planning, optimizing physical layouts, and incorporating FoMO-driven communication approaches.